Impact of Neonatal Factors and Nutrition on Kidney Size in 5-Year-Old Preterm-Born Children - Galu, Sorana C.; Hascoet, Jean-Michel; Vieux, Rachel (American Journal of Perinatology, 2015)
Objective The aim of this article is to evaluate the influence of neonatal factors on kidney size in 5-year-old preterm-born children.Study design Preterm-born children were examined at 5 years with kidney ultrasound.Result A total of 20 children were evaluated. Their gestational age (GA) was 29.3 ± 1.5 weeks, birth weight 1,321 ± 323 g. On Day 28, protein intake was (median, range) 2.8 (1.7–3.6 g/kg) g/kg, protein/total calories ratio 2.8 (range, 1.7–3.3 g/100 kcal) g/100 kcal. At 5 years, their systolic blood pressure was 97 mm Hg (range, 84–115 mm Hg). All had normal estimated glomerular filtration rate. Protein intake on Day 28 and protein/calories ratio on Day 28 were associated with a low total relative renal volume, respectively, β =  − 37 ± 15, p = 0.03; β =  − 50 ± 19, p = 0.03, after adjustment on GA, neonatal morbidities, and body mass index (multivariate linear regression). Kidney size was not associated with protein intake at 5 years.Conclusion Improving protein prescription in the neonatal period could have an impact on kidney size in childhood in preterm-born children.
Keywords: nutrition; neonates; kidney; very low birth weight